(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
When India became independent in 1947, only 15 medical colleges were created, and the total intake of students was 1000. The medical graduate schools steadily have been upgraded to colleges associated with separate universities. More than 500 medical universities operate in India today. Seven medical universities were set up in 1947 in Karnataka, but today there are 42 medical colleges alone. The Indian Medical Council in Delhi regulates the schools. The Indian Medical Council updates, reviews and recommends ways to develop teaching personnel, infrastructure services, and so on. The Medical Council of India The Indian Medical Council (MCI) proposes every year that all infrastructure, professional professionals and programmes be updated and strengthened for students.so, in this article we will discuss about background of medical college libraries in Hyderabad Karnataka region.